Evidence for shallow‐water 'Upper Kellwasser' anoxia in the Frasnian–Famennian reefs of Alberta, Canada. (11th March 2013) - Bond, David P. G.; Zatoń, Michał; Wignall, Paul B.; Marynowski, Leszek
<x xml:space="preserve">Abstract</x> The Frasnian–Famennian extinction witnessed the global devastation of both level‐bottom and reef communities in low latitudes. Marine extinctions in offshore level‐bottom communities are associated with two widespread, transgressive, anoxic 'Kellwasser Events' that support an anoxia–extinction link. Typical Kellwasser facies of bituminous limestones and shales are not obviously recorded in shallow‐water settings, and thus, it is unclear whether anoxia played a role in reef losses. We evaluate geochemical, petrographic and facies evidence for oxygen restriction from an extremely shallow‐water carbonate platform in Alberta. Sequence stratigraphy places the Frasnian–Famennian boundary at a sequence boundary that tops a laminated mudstone and interrupts carbonate platform deposition. Two transgressive pulses have been identified, one of which is associated with the second, major transgression of T‐R cycle IId of the Devonian eustatic sea‐level curve. Geochemical proxies indicate that these transgressions were accompanied by influx of dysoxic or anoxic waters. Organic carbon and U enrichment in the Frasnian, particularly just below the Frasnian–Famennian boundary, points to episodic dysoxic conditions that probably persisted into the basal Famennian and were coincidental with the global Upper Kellwasser Event. This study provides the first evidence for the smoking gun of an anoxia‐driven extinction in very shallow waters, implicating this potent killer in the demise of the Devonian reefs.